"Proposal for a Yoruba decimal counting system " (2010)
"Human activities involve the use of numbers everyday but there are only few explanations on how numbers came into existence. The Yoruba traditional number system, unlike other languages, employs the use o f addition, multiplication and subtraction which makes calculation complex, complicated and cumbersome. This has led many users-elites, traders, school children and the educated-to abandon its use. Today, alternative ways are being sought to Yoruba traditional counting and this paper presents the decimal number system and how to count in it up to one million with ease. It eliminates the subtractive numerals thus making counting in Yoruba easy and straight forward."